The Dynamic Consequences of State Building: Evidence from the French Revolution - Chambru, Cédric; Henry, Emeric; Marx, Benjamin (American Economic Review, 2024)
How do radical reforms shape economic development over time? In 1790, the French Constituent Assembly overhauled the kingdom’s organization to establish new local capitals. In some departments, the choice of local capitals over rival candidate cities was plausibly exogenous. We study how changes in administrative presence affect state capacity and development in the ensuing decades. In the short run, administrative proximity increases taxation and investments in law enforcement. In the long run, capitals obtain more public goods and grow faster. Our results shed light on the dynamic impacts of state building following one of history’s most ambitious administrative reforms. (JEL D70, H41, H71, O18, O43)